Drinking motives supporting binge drinking of Inuit adolescents - Decaluwe, Béatrice (Can J Public Health, 2019)
OBJECTIVES: Binge drinking has been identified as a public health concern among several Indigenous communities in Canada. Drinking motives have been shown to significantly influence drinking patterns among youth, but no research has been conducted among Inuit populations. This article assesses whether specific drinking motives are related to the number of binge drinking episodes among Inuit adolescents from Nunavik. METHODS: The data are drawn from the Nunavik Child Development Study, a longitudinal study conducted in the Canadian Arctic. Questions on alcohol use, binge drinking and drinking motives were asked to 174 adolescents (mean age of 18.5 years). Analyses of variance were used to test the relation between drinking motives and number of binge drinking episodes over the last year. RESULTS: Most Inuit participants mentioned drinking for enhancement reasons. A higher number of binge drinking episodes were reported among both adolescent males and adolescent females who frequently endorse enhancement motives, while social and coping motives have been exclusively related to binge drinking episodes among males. CONCLUSION: Findings highlight that motivational aspects supporting binge drinking among Inuit adolescents vary across sex and slightly contrast with studies conducted in non-Indigenous populations. Culturally relevant preventive interventions that target motivational aspects and take into account sex differences are needed.